Unmet Menstrual Hygiene Needs among the Impoverished Women, their Perceptions and Health Hazards - Sawina Somroo, Sidra Sarwar, Ifat Balouch, Maryam, Maria Ghafoor, Najma Bibi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Menstrual hygiene refers to the safe and easy access to menstrual products, infrastructure, information, and supplies, necessary for menstruating women to cope with their menstruation with decorum and console, along with systemic factors linking menstruation with health, empowerment and gender equality among other things. The effects of unmet menstrual hygiene needs on women’s health have been the subject of very little research. Women around the globe have widespread unmet-menstrual-health requirements, including the inability to access safe, clean facilities and cheap period supplies, which exposes them to socioeconomic depression and serious reproductive tract infections. Aims: Therefore, to determine the unmet menstrual hygiene needs of impoverished women, this study was conducted in the Southern region of Khyber Pakhtunkhwa, Pakistan, during the year 2021, to identify the women’s needs for menstrual hygiene, to rule out the risk of infections due to menstrual unhygienic, perceptions of females for unmet menstrual hygiene beyond affordable ranges and health hazards associated with it. Methods: The 1538 females took participation in the study, which investigated their unmet menstrual hygiene needs through an approved questionnaire in the area. Additionally, their period poverty, accessibility, and ability to acquire menstrual hygiene items were evaluated. Results: The average age range of the surveyed women was 28.50 + 3.12 (years) and their age at menarche was 11.8 + 2.4 (years). It was seen that a significantly higher percentage (P<0.05) of women (1506/1638; 97.91%), knew the use of menstrual pads to stop blood staining during menstruation, while, 2.66% of females knew how to use tampons. It was found that a significantly higher ratio (P<0.05) of women was suffering from the period property (59.68%) and most of them were deprived of using hygienic products in their menstrual cycle. Nonetheless, the majority of women used period pads (58.45%), followed by cotton (38.29%) and tampons (7.73%). While 9.03% (n=139/1538) of women were driven to use unsanitary diapers, rags, and other materials due to a lack of access to hygienic items, due to financial constraints. Significantly (P<0.05) less percentage of women were aware of the menstrual cycle (18.58%), the dangers of menstrual unhygienic (16.18%), and the risks of genital infections brought on by menstrual unhygiene (9.42%). But a substantially (P<0.05) larger fraction of females (1506/1638; 97.91%) were aware of using menstrual pads. However, just 2.66 percent of females knew how to use tampons, indicating that its use is not well known among women. The female population suffered from food insecurity at a rate of 17.94% and had a depressed socioeconomic position at a rate of 32.44%. Biological samples were obtained from 230 willing participants for the diagnosis of MHM-associated infections. Because urinary tract infections (UTI) and bacterial vaginosis (BV) are the two most prevalent illnesses linked with MHM in women, only 230 individuals consented to the collection of samples, which were then analyzed for these conditions in the laboratory. And 16% of females were revealed to have UTIs. While, 8.9 and 8.7% of females were infected with Trichomonas vaginalis and Gardnerella vaginalis bacterial vaginosis, respectively. Additionally, 6.1% of females had vaginal candidiasis. Practical implication: This study will create awareness among the general community that use of unhygienic products during menstruation are hazardous and may result in serious reproductive tract infections. Conclusion: According to the findings of our study, it was determined that due to their poverty, lower-class women lacked access to menstrual hygiene products, were susceptible to urinary and reproductive tract infections, and had a decreased socioeconomic standing in the community. Therefore, the government and non-government organizations should adopt stringent efforts to ensure gender equality and equity among menstruators and to assist low-income women in obtaining menstrual pads and other hygienic materials to protect their mental and physical health. Keywords: Bacterial vaginosis; Menstrual hygiene; Menstrual pads; Tampons; UTI.